Pengaruh Stres Kerja, Kecemburuan Sosial dan Lingkungan Kerja Terhadap Work Life Balance: (Studi pada Karyawan PT. Tri Adi Bersama Hub Halim Divisi Cargo Transport Jakarta Timur) - Mursal Azhari Lubis; Syaiful Anwar (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to determine the effect of work stress, social jealousy and work environment on work life balance in employees of PT. Tri Adi Bersama Hub Halim Cargo Transport Division, East Jakarta. Sampling using non-probability sampling technique with saturated sampling type totaling 50 people. Data were collected through questionnaires and analysis using multiple linear regression analysis. The results of the study showed that work stress had a significant negative effect on work life balance and the work environment had a significant positive effect on work life balance while social jealousy did not have a significant effect on work life balance in employees of PT. Tri Adi Bersama Hub Halim Cargo Transport Division, East Jakarta.